Curriculum dissemination in TAFE : a study of the educational change process in the Technical and Further Education sector in Western Australia - McBeath, Ursula Clare (Curtin University, 1994)
This research was concerned with identifying and finding solutions to serious dissemination problems existing in the curriculum change process in the Technical and Further Education (TAFE) sector in Western Australia. It explored the hypothesis that much of the frustration and inefficiency which occurs when TAFE courses are reviewed or upgraded can be eradicated by attention given to a well developed dissemination strategy.The research focused initially on four case studies of TAFE curriculum innovation and on the identification of the dissemination factors which the implementers believe affected them most. The difference between the ideal dissemination factors and the actual situation then was measured, and those considered most important in the dissemination process were identified. The findings then were brought together into a new dissemination strategy which was tested in the field with a newly accredited TAFE course.Three stages of research are reported. In the first stage, data for the case studies were collected through semi-structured interviews and then analysed to provide information for a questionnaire survey. The second stage, the survey, used a preferred and actual situation questionnaire, administered to 100 TAFE lecturers to gather measurable data on the factors affecting dissemination. Third, a dissemination strategy, consisting of tactics derived from the survey, the literature and from Curriculum Services staff, was put into place with the new Certificate of Horticultural Skills and its progress was observed and analysed as it affected the lecturers in the horticulture study area.The conclusions point to the importance of lecturer collaboration in the process of change and the need for TAFE administrators to employ a trained ‘change agent’ to encourage the development of teacher meaning and ownership. Shared development of teaching materials needs to be part of the change process. The existing ‘top-down’ mandated curriculum change process needs to exist alongside a ‘bottom-up’ involvement of lecturers, and change must be seen as a shared exercise between administrators and lecturers. It is recommended that the strategy evolved in this thesis be adopted for further TAFE curriculum projects and that it be evaluated and modified for universal application in the TAFE curriculum change process.